Protein C Activity in Healthy Volunteers - Influence of Age, Sex, Smoking and Oral Contraceptives - Tait, R C; Walker, Isobel D; Islam, S I A M; McCall, Frances; Conkie, J A; Wight, M; Mitchell, R; Davidson, J F (Thrombosis and Haemostasis, 1993)
Interpretation of protein C (PC) levels in a given individual has several limitations. A normal PC activity does not necessarily exclude a genetic deficiency nor can a reduced level confirm it. Measuring PC amidolytic activity in 9,648 healthy blood donors has allowed identification of demographic factors which cause variation in PC activity and further hinder interpretation. PC activity displays a log normal distribution and significant variation with age. This is most marked in young adult males when mean PC activity rises from 0.86 iu/ml (15–19 years) to 1.04 iu/ml (45–49 years; P <0.0001). Pre-menopausal females, who for most age ranges, have mean PC activity below their male contemporaries, show a less marked rise with age until the menopause when PC activity rises further. The use of hormonal contraceptive preparations is associated with an increase in mean PC activity of 0.05–0.08 iu/ml while smoking habit has no influence on PC activity.In view of these findings we strongly recommend the use of age and sex restricted reference ranges when interpreting PC activity.